MENINGKATKAN HASIL BELAJAR PKN MELALUI PENERAPAN PEMBELAJARAN KOOPERATIF TIPE JIGSAW SISWA KELAS IV SD NEGERI 012 SILIKUAN HULU KECAMATAN UKUI - Sudahana ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2017)
This research was motivated by lack of civics student learning outcomes. Low student learning outcomes is caused by: (a) the teaching methods teachers are passive and monotonous; and (b) the students were cool to mess around when lessons. This study aims to improve student learning outcomes. This research is a class act, performed in SD Negeri 012 Silikuan Hulu. The data used in this study is the activity data of teachers and students as well as civics student learning outcomes. Based on the results of the study revealed that the activities of teachers and students and the learning outcomes of students has increased. This is evidenced by the acquisition: the preliminary data the number of students who completed is 10 students, an increase in the first cycle by the number of students increased to 15 students and 17 students in the second cycle. Teacher activity also increased in the first cycle of meeting 1 percentage teacher activity by 47%, in the first cycle of meeting 2 increased with the percentage of 56%. In the second cycle 1 meeting increased to 68% and the second cycle 2 meeting increased to 73%. Student activity also increased in the first cycle 1 meeting a percentage of student activity by 50%, in the first cycle of meeting 2 increased with the percentage of 57%. In the second cycle 1 meeting increased to 65% and the second cycle 2 meeting increased to 82%.